Embracing Defects and Disorder in Magnetic Nanoparticles. Issue 7 (15th February 2021) - Lak, Aidin; Disch, Sabrina; Bender, Philipp
Abstract: Iron oxide nanoparticles have tremendous scientific and technological potential in a broad range of technologies, from energy applications to biomedicine. To improve their performance, single‐crystalline and defect‐free nanoparticles have thus far been aspired. However, in several recent studies, defect‐rich nanoparticles outperform their defect‐free counterparts in magnetic hyperthermia and magnetic particle imaging (MPI). Here, an overview on the state‐of‐the‐art of design and characterization of defects and resulting spin disorder in magnetic nanoparticles is presented with a focus on iron oxide nanoparticles. The beneficial impact of defects and disorder on intracellular magnetic hyperthermia performance of magnetic nanoparticles for drug delivery and cancer therapy is emphasized. Defect‐engineering in iron oxide nanoparticles emerges to become an alternative approach to tailor their magnetic properties for biomedicine, as it is already common practice in established systems such as semiconductors and emerging fields including perovskite solar cells. Finally, perspectives and thoughts are given on how to deliberately induce defects in iron oxide nanoparticles and their potential implications for magnetic tracers to monitor cell therapy and immunotherapy by MPI. Abstract : Recent developments in the emerging research field of defect‐engineering in magnetic nanoparticles and its beneficial impact on magnetic hyperthermia performance of nanoparticles are presented. Different fields of research relevant to magnetic nanoparticles from synthesis to magnetic structure determination and biomedical applications are covered, considering defects and associated magnetic disorder at different length scales.